(untitled) (City: History, Culture, Society, 2023)
The research examines the history and architecture of a residential building erected in the 18th century and completed in the 19th century, located in the centre of Kyiv’s Podil district. For the first time, this building garnered the attention of Kyiv experts in 1930, when F. Ernst published an article about it in the guidebook Kyiv. Further studies, which reinvigorated in the late 1970s, included an architectural study and a search for documents in Kyiv archives to shed light on the history of ownership of this building. In the latter half of the 1980s and the early 1990s, Kyiv architects (O. Shevchenko, V. Petrushchenko, I. Malakova, V. Otchenashko, A. Podolskyi, V. Havryliuk), art critics (M. Kadomska, L. Pliashko), and archivists (R. Liakina) conducted extensive research on the structure at 16B Spaska Street. Their investigations led to significant insights into the various construction phases of the building and revealed the names of its owners from the 1780s to 1917, including the Kyiv merchants Sychevski, Usovychi, Khotyanovski, Pokrovski, and Morachevski. From 1989 to 1993, restoration works aimed to restore the original façade of this building, built at several stages: in the 18th century (most of the first floor and cellars), in the first quarter of the 19th century, and at the end of the 19th century (second floors). The completion of these restorations led to the foundation of the Hetmanship Museum at 16B Spaska Street. The precise construction date of this unique example of civil structure in Kyiv remained a subject of debate among scholars. The time of the building’s construction is estimated to fall between the late 1780s and the 1790s. We came to such conclusions with the integration of a comprehensive array of historical sources, primarily Ukrainian architectural analogies. After all, this era marked the onset of active civil brick construction in Kyiv’s Podil, lasting until the fire of 1811, which destroyed almost all the buildings of this historical city district. The surviving ’stone houses’ of Podil, including the building on 16B Spaska Street, today stand as rare architectural and historical treasures, reminiscent of Kyiv’s 18th-century civil construction.